2019
DOI: 10.1088/1741-4326/ab25cb
|View full text |Cite
|
Sign up to set email alerts
|

Physics research on the TCV tokamak facility: from conventional to alternative scenarios and beyond

Abstract: The research program of the TCV tokamak ranges from conventional to advanced-tokamak scenarios and alternative divertor configurations, to exploratory plasmas driven by theoretical insight, exploiting the device’s unique shaping capabilities. Disruption avoidance by real-time locked mode prevention or unlocking with electron-cyclotron resonance heating (ECRH) was thoroughly documented, using magnetic and radiation triggers. Runaway generation with high-Z noble-gas injection and runaway dissipation by subsequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 82 publications
0
55
0
Order By: Relevance
“…The authors would like to thank the entire TCV team (see author list of 22 ) for making these experiments possible and are especially grateful to Dr. Labit for his expertize on and modifications to the small-ELM plasma scenario. Furthermore, the entire EUROfusion MST1 team (see author list of 41 ) is greatly acknowledged, in particular input from Dr. Bernert.…”
Section: Acknowledgementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors would like to thank the entire TCV team (see author list of 22 ) for making these experiments possible and are especially grateful to Dr. Labit for his expertize on and modifications to the small-ELM plasma scenario. Furthermore, the entire EUROfusion MST1 team (see author list of 41 ) is greatly acknowledged, in particular input from Dr. Bernert.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…In this paper we demonstrate a strategy to control impurity emission front locations, as a proxy for divertor detachment, on the Tokamak Configuration Variable (TCV) 22 . (i) We apply real-time analysis of multi-spectral video images obtained from the MANTIS diagnostic 23 to reconstruct the poloidal location of a chosen spectral line’s emission front.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, much effort is directed towards the development of schemes to avoid, limit or mitigate the formation of such a beam. One proposed measure is using massive material injection (MMI) in the form of gas (massive gas injection – MGI) or frozen pellets (shattered pellet injection) to avoid or dissipate the runaway electrons (Hollmann et al 2015 a ; Lehnen et al 2015), and its efficiency has been demonstrated in medium-sized tokamaks (Hollmann et al 2015 b ; Reux et al 2015; Pautasso et al 2016; Esposito et al 2017; Paz-Soldan et al 2017; Carnevale et al 2018; Coda et al 2019; Mlynar et al 2019; Pautasso et al 2020). However, the plasma currents, temperatures and densities of future devices such as ITER will be significantly larger than what can be achieved in current experiments, and simulations are necessary to foresee the effectiveness of massive material injections for disruption mitigation under such conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Turbulence spreading is also important for the turbulence in the scrape-off-layer (SOL), where the turbulence spreading from the pedestal region is expected to be more dominant than the locally driven turbulence [243]. There are many experiments reported regarding the broadening of the radial profile of heat flux and the increase of power decay length, that are required for the reduction of the heat load on the divertor in tokamaks [267][268][269][270]. Since enhancement of turbulence in SOL is one of the candidates for broadening of the radial profile of heat flux, deeper understanding of turbulence in SOL is an emerging issue in the future.…”
Section: Discussionmentioning
confidence: 99%